Strengthening Student Character Through Qur’anic Values in Islamic Education - Syamsuri Syamsuri; Awaliah Musgamy (Journal La Edusci, 2025)
This study explores how Islamic education grounded in Qur’anic values strengthens the character of students through pedagogical practices implemented by teachers in an Islamic school context. Using a qualitative descriptive design, the research investigates how teachers interpret Qur’anic values, integrate them into instructional activities, and employ strategies to ensure the internalization of moral principles among students. Data were collected through in-depth interviews, classroom observations, and documentation review, and analyzed using the Miles and Huberman model of data condensation, display, and conclusion drawing. The findings show that teachers view Qur’anic values not as abstract religious concepts but as practical ethical guidelines that must be embedded into daily behavior, interpersonal interactions, and learning routi9nes. Integration occurs through lesson planning infused with moral objectives, value-centered classroom activities, reflective dialogue, and narrative-based instruction that links Qur’anic teachings with real-life situations. Teachers also employ strategies such as habit formation, experiential moral tasks, compassionate discipline, and role modeling to facilitate character internalization. These practices collectively form a moral ecosystem that enables students to experience, practice, and reflect upon Qur’anic ethics in their daily school life. The study concludes that the effectiveness of Qur’anic-based character education depends on its holistic implementation, where values are consistently demonstrated by teachers, reinforced within the learning environment, and absorbed through continuous behavioral and spiritual engagement. This research contributes to a deeper understanding of Islamic pedagogy and highlights the importance of integrating Qur’anic values in nurturing morally grounded and socially responsible learners.